KONTRASEPSI VASEKTOMI PADA AKSEPTOR KB PRIA DI KECAMATAN TAPUNG HILIR - Lutfinanda Rizka Pradipta; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research is motivated KB Low participation of men with vasectomies in some areas in Kampar, but not so for the District of Tapung Downstream vasectomy acceptors numbers increasing from year to year. The success of family planning programs in Kampar affected by these individual motivation to do their best in order to achieve the desired objectives. Dissemination and promotion of family planning, especially men with vasectomies can Rekanalisas reconnection of the vas deferens and not permanent sterilization, had a huge impact on men's participation in family planning Tapung Downstream vasectomy. The research method used in the study authors are descriptive research method. Supporting factor is the availability of health resources in the District Tapung Downstream, wherein regarding health care facilities, affordability of health resources, priorities and the government's commitment to health and health skills. Furthermore, the driving factor in the District Tapung Downstream men to join KB vasectomy is a factor that pushed for the occurrence of a particular behavior, in which there are opinions, support, good criticism of the family, especially his wife, co-workers, community leaders, religious leaders, as well as from health workers themselves. All of these factors are determinants of a man to act as a family planning vasectomy. This is consistent with the perspective of social action proposed Parson, human action is based on motivational orientation and orientation values available in the environment in which he lived.Key word : Vasektomi, Kontrasepsi dan Tindakan Sosial